2019
DOI: 10.1145/3373464.3373474
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Multi-Label Topic Models

Abstract: Every day, an enormous amount of text data is produced. Sources of text data include news, social media, emails, text messages, medical reports, scientific publications and fiction. To keep track of this data, there are categories, key words, tags or labels that are assigned to each text. Automatically predicting such labels is the task of multi-label text classification. Often however, we are interested in more than just the pure classification: rather, we would like to understand which parts of a text belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Alghamdi and Alfalqi (2015) compare 4 topic models (LDA, LSI, PLSA and CTM): this survey studied both their capability in modelling static topics, as well as in detecting topic change over time, highlighting the strengths and weaknesses of each. Burkhardt and Kramer (2019) provide a survey for the adjacent task of multi-label topic models, underlining its challenges and promising directions. Qiang et al (2020) give an extensive performance evaluation of multiple topic models in the context of the Short Text Topic modelling sub-task (e.g.…”
Section: Topic Models Comparisonmentioning
confidence: 99%
“…Alghamdi and Alfalqi (2015) compare 4 topic models (LDA, LSI, PLSA and CTM): this survey studied both their capability in modelling static topics, as well as in detecting topic change over time, highlighting the strengths and weaknesses of each. Burkhardt and Kramer (2019) provide a survey for the adjacent task of multi-label topic models, underlining its challenges and promising directions. Qiang et al (2020) give an extensive performance evaluation of multiple topic models in the context of the Short Text Topic modelling sub-task (e.g.…”
Section: Topic Models Comparisonmentioning
confidence: 99%
“…L-LDA has been widely applied for efficiency and concision, but it constrains the topic distributions in the observed labels that lead to over-focus on them. To alleviate this problem, Dependency-LDA (Rubin et al, 2011) incorporates another topic model to model the observed label correlations, which is deemed to be crucial for multi-label classifiers (Burkhardt and Kramer, 2019b). Another recent improved approach of L-LDA is Twin labeled LDA (Wang et al, 2020b), which employs two sets of parallel topic modeling processes, one incorporates the prior label information by hierarchical Dirichlet distributions, the other models the grouping tags that have prior knowledge about the label correlation.…”
Section: Related Workmentioning
confidence: 99%
“…Statistical topic modeling approaches (Blei, 2012), e.g., Latent Dirichlet Allocation (LDA) (Blei et al, 2003), have been widely applied in the field of data mining, latent data discovery, and document classification (Jelodar et al, 2018). Standard LDA is a completely unsupervised algorithm, and then how to incorporate prior knowledge into the topic modeling procedure is a popular research direction (Burkhardt and Kramer, 2019b;Chen et al, 2019). A major challenge of these LDA customizations is the computational cost of computing the posterior distribution.…”
Section: Introductionmentioning
confidence: 99%
“…There are different types of topic classification depending on the dataset nature, such as Binary-class and Multi-class, while this paper addresses the scientific articles' topic classification which falls in the type of Multi-labeled Topic classification [2]. In which each article can be assigned to one or more classes.…”
Section: Introductionmentioning
confidence: 99%